Perancangan Interior Edy Pirih Boxing Camp di Surabaya - Adi Santosa, Brian Suryanata (Intra, 2015)
Sports boxing in Surabaya branch in reality do not have adequate space and facilities, ranging from the standard and inadequate led to the growth of boxing underdeveloped and young seedlings that have no boxing talent can develop their potential well. Through interior design that implements the concept of